Effects of stress (aging) on Enchytraeus crypticus: an omics approach - Neves, Ana Beatriz Pires das (2023)
Although aging research has historically been focused on humans and human health, interest in understanding the aging process and aging phenotypes in different organisms has been gaining interest, for different reasons. In ecotoxicology, tests usually follow standard guidelines that use healthy individuals. However, natural populations are comprised of animals of different ages, that will have different degrees of vulnerability to the action of e.g. pollutants in the environment. Thus, current hazard assessment might underestimate the effects of stressors in natural populations. To better cover the impact of age as a factor in ecotoxicity testing, research should pursue a better understanding of aging in environmentally relevant species (namely at the cellular and molecular level). This study aimed at providing a more fundamental understanding of aging in a soil ecotoxicology model species, Enchytraeus crypticus (Oligochaeta), by assessing age-related gene expression changes for organisms aging in soil for 34, 146 and 202 days. E. crypticus are important members of the saprophagous mesofauna, and their use as model organisms in ecotoxicology is backed up by a remarkable array of molecular tools (e.g., transcriptomic, proteomic, metabolomic and epigenetic). Results showed a clear pattern of downregulation with age, which could relate to stochastic DNA damage driving transcriptional stress. Among downregulated genes were the target genes related to insulin signalling, telomere length regulation and oxidative phosphorylation, as well as genes related to RNA transcription or neuronal excitability. Most target genes involved in mTOR signalling and stress response were also downregulated. This pattern of downregulation could ultimately be driving the aging process, by contributing to the dysregulation of the corresponding processes. At day 202, three genes were upregulated - TSC2 (a negative regulator of mTORC1), HSP70 and HSP90 (two chaperones with important functions in response to stress). This might indicate an attempt to mitigate these age-induced changes. The present study could be a first step to understand the molecular processes driving aging in E. crypticus. To interpret this knowledge, research with proteomic, metabolomic or epigenetic tools could be followed. Ultimately, this new knowledge could help evaluate the impact of e.g. environmental pollution in aged individuals and natural, heterogeneous populations.